Mechanical properties and water resistance of cellulosic fiberboards with soybean protein based adhesives - Li, Xin (Kansas State University, 2012)
Large amount of fiberboard are used for packaging applications every year, which generate a large amount of solid wastes causing environmental pollution if these packaging materials are not recycled. Also, a large amount of wood are needed for making fiberboard, which is limited resource in the earth. Reducing the weight of fiberboard and recycling the fiberboard materials are two methods to save quantities of wood fiber in fiberboard manufacture, which benefit the environment and economy. Besides, most adhesives used for producing the fiberboard contain environmental hazardous chemicals. It is necessary to develop new technology to produce cellulosic fiberboards with environmental friendly bio-based adhesives. The soybean is an agricultural product, and its resource is abundant. Soybean protein is a bio- material that offers an alternative to the existing synthetic adhesives to reduce petroleum dependence of the U.S. energy strategy. The newly developed soy-based adhesive is also competitive in cost. Material cost based on food-grade soybean protein is around 20 cents/Lb. The cost of commercial PF resin is about 14 ~ 17 cents/Lb. Price of hot-melt adhesive for fiberboard is around $6/Lb. In this study, soybean protein was modified with sodium dodecyl sulfate as an adhesive for two bio-based fiberboards products, medium density fiberboard by dry processing and light weight cardboard by wet processing. The mechanical and water soaking properties of these cellulosic fiberboards were stronger than or as same as commercial solid fiberboard. This research suggests that these cellulosic fiberboards with modified soybean protein based adhesive have great potential as alternative to current commercial fiberboard.
Keywords: Fiberboard; Mechanical property; Water soaking; Soybean; Adhesives; Agriculture, General (0473)